2018
DOI: 10.7554/elife.37024
|View full text |Cite
|
Sign up to set email alerts
|

Altered bone growth dynamics prefigure craniosynostosis in a zebrafish model of Saethre-Chotzen syndrome

Abstract: Cranial sutures separate the skull bones and house stem cells for bone growth and repair. In Saethre-Chotzen syndrome, mutations in TCF12 or TWIST1 ablate a specific suture, the coronal. This suture forms at a neural-crest/mesoderm interface in mammals and a mesoderm/mesoderm interface in zebrafish. Despite this difference, we show that combinatorial loss of TCF12 and TWIST1 homologs in zebrafish also results in specific loss of the coronal suture. Sequential bone staining reveals an initial, directional accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 46 publications
6
72
1
Order By: Relevance
“…Cranial vault formation requires a wellorchestrated set of genes, which controls the differentiation of mesenchymal cells into mature osteoblasts; this enabled us to identify several clusters(Figure 6D, E). Our expression analysis of the twist genes involved in osteoprogenitor regulation revealed that clusters 0, 1, 3, 5, 9, 12, and 13 contained osteoprogenitor cells (OP0 to OP5)(Morgan et al, 2011,Teng et al, 2018…”
mentioning
confidence: 99%
“…Cranial vault formation requires a wellorchestrated set of genes, which controls the differentiation of mesenchymal cells into mature osteoblasts; this enabled us to identify several clusters(Figure 6D, E). Our expression analysis of the twist genes involved in osteoprogenitor regulation revealed that clusters 0, 1, 3, 5, 9, 12, and 13 contained osteoprogenitor cells (OP0 to OP5)(Morgan et al, 2011,Teng et al, 2018…”
mentioning
confidence: 99%
“…Twist genes are expressed in osteoprogenitors and regulate proliferation and differentiation of these cells. ( 10,32,33 ) Therefore, we decided to call those clusters “osteoprogenitors” with progressive numbers from 0 to 5 (OP0 to OP5) based on their level of differentiation as described in the following paragraphs (Fig. 6 E ).…”
Section: Resultsmentioning
confidence: 99%
“…As EMT transcription factors, twist1 are involved in neural crest migration, which undergo an EMT to give rise to many different derivatives [46]. Regulated by thyroid hormone [47], retinoic acid (RA) [48], Wnt [49], Bmps and Id2a [28] signaling pathways, Twist 1a/b is required for proper development of craniofacial cartilage and skeleton [50], with Runx2 a known downstream target [13,14]. Twist1 is also involved in blood vessel sprouting in zebrafish embryos [51].…”
Section: Discussionmentioning
confidence: 99%